Дослідження геоелектричними методами інженерно- геологічного стану південно-західного Кривбасу. Частина 3. Результати застосування геоелектричних методів привирішенні інженерно-геологічних завдань - Пігулевський, П.Г.; Свистун, В.К.; Кирилюк, О.С. (Геоінформатика, 2017)
Проаналізовано можливості ефективного використання геоелектричних методів при вивченні інженерно- геологічного стану території Кривбасу та впливу техносфери на її гідрогеологічне середовище. В третій частині статті за результатами досліджень геоелектричними методами, проведених у різні роки, та за їх комплексування з геолого-гідрогеологічними спостереженнями подано 3D моделі зміни геоелектричних параметрів за латераллю і глибиною та результативні карти зволоження (“підтоплення”) досліджуваної площі за чотирирічний період з 2008 по 2012 р. під впливом природних чинників та дії гідротехнічних споруд. Ці матеріали у сукупності з результатами попередніх геолого-геофізичних досліджень дали змогу отримати карту інженерно-геологічного стану Південно-Західного Кривбасу. Наведено практичні приклади використання результатів досліджень геоелектричними методами з уточненням і конкретизацією деяких окремих особливостей гідрогеологічного та інженерно-геологічного стану території регіону залежно від антропогенного впливу на її геоекологічні умови. Анализируются возможности эффективного использования геоэлектрических методов при изучении инженерно-геологического состояния территории Кривбасса и влияния техносферы на ее гидрогеологическую среду. В третьей части статьи по результатам проведенных в разные годы исследований геоэлектрическими методами и их комплексированию с геолого-гидрогеологическими наблюдениями рассмотрена 3D модель изменений геоэлектрических параметров по латерали и глубине и представлена результативная карта увлажнения (“подтопления”) исследуемой площади за 4-летний период с 2008 по 2012 г. под влиянием естественных и гидротехнических сооружений. Эти материалы в совокупности с результатами предыдущих геолого-геофизических исследований позволили построить карту инженерно-геологического строения Юго-Западного Кривбасса. Приведены практические примеры использования результатов исследований геоэлектрическими методами с уточнением и конкретизацией некоторых отдельных особенностей гидрогеологического и инженерно-геологического состояния территории региона в зависимости от антропогенного влияния на ее геоэкологическую обстановку. Purpose. The aim of the article is to apply geophysical surveys to studying engineering-geological conditions of the south-western part of Kryvbas in solving problems of ecological safety.
Design/methodology/approach. Analysis of the changes of geo-electric resistance in the four years from 2008 till 2012 and hydrogeological studies of wells observation allowed us to establish their connection with fluctuations in the water level over this period and obtain an analytical equation to determine the component of “flooding” in the first surface of the aquifer.
Joint processing of geoelectric studies carried out at 1983 and 2008 permitted to obtain a detailed geotechnical zoning study area.
Findings. Based on the results obtained, research maps were made which clarify and specify the features of the geoelectric state of the investigated area both in three-dimensional space and time (the period from 2008 till 2012). Using analytical equations to determine the component of “flooding” in the first surface of the aquifer made it possible to build a productive map showing the impact of natural and hydraulic engineering works in the study area for the four-year period. The data of geoelectric studies carried out at 1983 and 2008, together with the results of the previous geological and geophysical studies, allowed us to make a detailed map of the engineering-geological condition of southwest of Kryvbas.
We have given practical examples of applying the research results of geoelectric methods to clarifying and specifying particular features of the hydrogeological and geotechnical conditions depending on the anthropogenic impact on the geoecological situation of the south-western Kryvbas.
Practical value/implications. The proposed technology of research can quickly detect and map the zones of flooding by geoelectric methods and increase the accuracy of engineering and geological zoning for complex study of the effect of the technosphere on the geological environment of Kryvbas in solving problems of ecological safety.